Laptop ownership and use among educators: Reflections from school teachers in Malaysia - Md. Khambari, Mas Nida; Moses, Priscilla; Wong, Su Luan (International Journal of Instruction, 2009)
This research explored the experiences of owning and using laptops among three secondary school teachers in Malaysia. They were granted personal laptops by the Ministry of Education through the Teaching and Learning of Science and Mathematics in English, or known as Pengajaran dan Pembelajaran Sains dan Matematik dalam Bahasa Inggeris (PPSMI) programme. This document has no comments. PPSMI was aimed at enhancing the teaching of these subjects in English with the aid of technology. The research adopted a case study qualitative approach using semi-structured interviews. Three in-depth interviews were audio recorded in the teachers’ schools, transcribed and analysed. Several themes related to the benefits and challenges of owning and using laptops emerged from these interviews. This paper, therefore, also seeks to discuss these themes in detail.